Determinants of Relapse Among Schizophrenia Patients in West Kalimantan: A Cross-sectional Study - Wahyu Kirana; Dewin Safitri; Yunita Dwi Anggreini (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
Relapse can affect functional impairment, rehospitalization, readmission, and long-term disability among schizophrenia patients. Although several factors, such as medication adherence, internalized stigma, and family support, are recognized as determining factors, there is still limited evidence from the Indonesian context, especially in West Kalimantan. This study aimed to evaluate the factors associated with relapse among schizophrenia patients. A quantitative, cross-sectional design was conducted at a mental hospital in West Kalimantan. A total of 63 patients and their families participated in this study, selected using a consecutive sampling technique. The MMAS-8, ISMI-9, and family support questionnaires were used to collect the data; patients completed the MMAS-8 and ISMI-9 questionnaires directly, whereas their families completed the family support questionnaire using a Google Form. The patients' medical reports were used to identify the relapse rate. Data were analyzed using Fisher's exact test and multivariate logistic regression.? Fisher's exact test showed that medication adherence was significantly associated with relapse (p = 0.02, p < 0.05), while internalized stigma and family support were not associated (p = 0.21; p = 0.12, p > 0.05). Medication adherence was the strongest factor associated with relapse, with an Adjusted Odds Ratio (AOR) of 2.091. This finding suggests that schizophrenia patients with a low level of medication adherence were over two times more likely to experience a lifetime relapse compared to those with a higher level of medication adherence?Keywords: ?Family Support, Internalized Stigma, Medication Adherence, Relapse, Schizophrenia